2022
DOI: 10.1371/journal.pone.0276080
|View full text |Cite
|
Sign up to set email alerts
|

Improved jellyfish gelatin quality through ultrasound-assisted salt removal and an extraction process

Abstract: The use of by-products of salted jellyfish for gelatin production offers valuable gelatin products rather than animal feed. Several washes or washing machines have reported removing salt in salted jellyfish. However, the green ultrasound technique has never been reported for the desalination of salted jellyfish. The objectives were to determine how effectively the raw material’s salt removal was done by combining the traditional wash and then subjected to the ultrasonic waves in a sonication bath for 20–100 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Compared to the same desalted jellyfish by-product, the sample was washed using a sonication bath, pre-treated with 0.2 M hydrochloric acid (HCl), and extracted at 80 • C for 4, 6, and 8 h. The results indicated that the gelatin yield was 7.43-32.69%. The highest gelatin yield obtained in this study was similar to that for the sample extracted at 80 • C for 8 h, at 32.69% [28]. The gelatin yield of the WO48 sample was higher than that in the previous work, which may have resulted from the raw material and extraction time.…”
Section: Gelatin Yieldsupporting
confidence: 52%
See 3 more Smart Citations
“…Compared to the same desalted jellyfish by-product, the sample was washed using a sonication bath, pre-treated with 0.2 M hydrochloric acid (HCl), and extracted at 80 • C for 4, 6, and 8 h. The results indicated that the gelatin yield was 7.43-32.69%. The highest gelatin yield obtained in this study was similar to that for the sample extracted at 80 • C for 8 h, at 32.69% [28]. The gelatin yield of the WO48 sample was higher than that in the previous work, which may have resulted from the raw material and extraction time.…”
Section: Gelatin Yieldsupporting
confidence: 52%
“…The imino acid content in mammalian gelatin was reportedly higher than that in marine gelatin [30]. Compared to gelatin extracted from jellyfish in previous works, the gel strength of the WU24 sample in this work was higher than that of the desalted jellyfish by-product gelatin after the sample was treated with 0.1 M HCl and extracted at 60 • C for 12 h (323.74 g) [27]; the desalted jellyfish by-product gelatin obtained when the sample was washed using a sonication bath for 40 min, pre-treated with 0.2 M HCl, and extracted at 80 • C for 4 h (447.01 g) [28]; and cannonball jellyfish gelatin soaked in 1.5% citric acid and extracted at 60 • C for 4.5 h (3.4 g) [31]. Compared to other marine gelatin samples, the gel strength of the WU24 sample showed lower strength than that of the tilapia skin gelatin after the sample was pre-treated with pepsin enzyme (5 units/g of the sample) and extracted at 55 • C for 6 h (725 g) [32].…”
Section: Gel Strengthmentioning
confidence: 70%
See 2 more Smart Citations